Simple Method f or Spectrophotometric Determination o f Benzidine i n Aqueous Solutions b y Coupling w ith Β - Naphthol - Hamed, Ameera H (Al-Nahrain Journal of Science, 2018)
Anew simple and rapid colorimetric method has been developed for the determination of benzidine in aqueous solutions. The method is based on the formation of a pink colored azo dye by diazotization of benzidine, followed by a diazo-coupling reaction between the resulting product and β-naphthol. The maximum absorbance of azo dye at 525 nm. Beer's law was found to be obeyed in the concentration range of 0-12 µg. ml1 with molar absorptivity 12360 L. mol1. cm1. The optimum reaction conditions and other analytical parameters were evaluated.